Plant cell biology - edited by Chris Hawes and Béatrice Satiat-Jeunemaitre (Oxford University Press, 2001)
The book covers a substantial range of methods for working on living cells, including the application of fluorescent probes, cytometry, expression systems, the use of green fluorescent protein, micromanipulation and electrophysiological techniques. Also featured are chapters on macromolecular location procedures involving immunocytochemistry and in situ hybridisation, and the book concludes with a range of biochemical techniques for the isolation of cytoplasmic organelles